A Cross-sectional bioassessment of ecological integrity using SASS5 in the Umngeni, Thukela, Umvoti, Umdloti, and Umfolozi rivers, KwaZulu-Natal. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2025)
Background Freshwater ecosystems provide essential biodiversity and ecological services but face increasing threats from urbanization, agriculture, and industrial discharge. In South Africa, the South African Scoring System version 5 (SASS5) is widely used to monitor river health through macroinvertebrate community responses. This study assessed the ecological integrity of five major rivers in KwaZulu-Natal, uMngeni, Thukela, Umvoti, Umdloti, and Umfolozi, using SASS5 to evaluate biotic responses to environmental stress across spatial gradients. Methods A cross-sectional bioassessment was conducted between October and December 2024 at 15 sites (upstream, midstream, and downstream per river). Macroinvertebrates were sampled using SASS5 protocols across different biotopes. Taxa were identified to family level, with SASS5 scores and Average Score Per Taxon (ASPT) calculated. Physical habitat quality was assessed using the Index of Habitat Integrity (IHI). Statistical analyses, including Pearson’s correlation, were used to evaluate relationships between habitat quality and biotic indices across sites. Results Substantial spatial variability was observed. The uMngeni and Umvoti Rivers recorded the lowest downstream scores (SASS5: 48 and 52; ASPT: 4.2 and 4.4, respectively), indicating poor ecological condition due to urban and industrial pollution. In contrast, Umdloti and Umfolozi Rivers displayed higher scores, reflecting better habitat quality and ecological integrity. The Thukela River showed moderate scores with downstream decline. A significant positive correlation between SASS5 scores and IHI (r = 0.76, p < 0.01) confirmed that better habitat conditions supported healthier macroinvertebrate communities. Conclusion River health in KwaZulu-Natal is highly variable, with downstream sections most impacted by anthropogenic stress. SASS5 proved effective in detecting ecological degradation across spatial gradients. Recommendation Integrated biomonitoring using SASS5, habitat, and water quality assessments is recommended. Degraded downstream reaches should be prioritized for restoration via land-use management, pollution control, and community-based monitoring.